Brain bioenergetics and redox state measured by (31)P magnetic resonance spectroscopy in unaffected siblings of patients with psychotic disorders - Chouinard, Virginie-Anne (Schizophr Res, 2017)
BACKGROUND: Brain bioenergetic anomalies and redox dysregulation have been implicated in the pathophysiology of psychotic disorders. The present study examined brain energy-related metabolites and the balance between nicotinamide adenine dinucleotide metabolites (oxidized NAD+ and reduced NADH) using (31)P-magnetic resonance spectroscopy ((31)P-MRS) in unaffected siblings, compared to first episode psychosis (FEP) patients and healthy controls. METHODS: 21 unaffected siblings, 32 FEP patients (including schizophrenia spectrum and affective psychoses), and 21 controls underwent (31)P-MRS in the frontal lobe (6×6×4 cm(3)) on a 4T MR scanner, using custom-designed dual-tuned surface coil with outer volume suppression. Brain parenchymal pH and steady-state metabolite ratios of high energy phosphate compounds were measured. NAD+ and NADH levels were determined using a (31)P-MRS fitting algorithm. 13 unaffected sibling-patient pairs were related; other patients and siblings were unrelated. ANCOVA analyses were used to examine (31)P-MRS measures, with age and gender as covariates. RESULTS: The phosphocreatine/adenosine triphosphate ratio was significantly reduced in both unaffected siblings and FEP patients, compared to controls. NAD+/NADH ratio was significantly reduced in patients compared to siblings and controls, with siblings showing a reduction in NAD+/NADH compared to controls that was not statistically significant. Compared to patients and controls, siblings showed significantly reduced levels of NAD+. Siblings did not differ from patients or controls on brain pH. DISCUSSION: Our results indicate that unaffected siblings show some, but not all the same abnormalities in brain energy metabolites and redox state as FEP patients. Thus, (31)P-MRS studies may identify factors related both to risk and expression of psychosis.